Changes of Dry Eye Parameters Especially Meibomian Gland Functions After Punctal Plugs Insertion in Aqueous-Deficient Dry Eye Patients - Liu, Tingting; Liu, Shulin; Gan, Meiqi; He, Yuqin; Fu, Hongxue; Xu, Mei (Frontiers in Medicine, 2022)
Background: The study aimed at investigating the changes of dry eye parameters, especially the meibomian gland function in dry eye patients with primary Sjögren’s syndrome (SS) and non Sjögren’s syndrome (non-SS) before and after punctal plugs insertion. Material and Methods: SS and non-SS dry eye patients received punctal plugs insertion were prospectively investigated. This study recruited fifty patients. The standardized patient evaluation of eye dryness (SPEED), ocular surface disease index (OSDI), tearmeniscus height (TMH), Noninvasive Keratographic breakup time(NIKBUT), Schirmer test without anesthesia (Schirmer I Test, SI T), corneal fluorescein staining (CFS), the meibomian gland dropout (meiboscore), meibum expressibility score (MES), meibum quality score (MQS), lid margin abnormalities and the lipid layer thickness(LLT) were analyzed at pre-obstruction, 2 weeks, 2 and 6 months following the obstruction. Results: Our study observed a statistically significant improvement in ocular symptom scores (SPEED and OSDI scores) after punctal plugs insertion at every visit in both SS and non-SS patients (all p<0.05). A similar pattern was observed in TMH, SI T, NIKBUT and CFS score in both groups (all p<0.05), except that NIKBUT and CFS score had no obvious change in SS group at 6 months (P>0.05). In terms of the meibomian gland evaluation, meiboscore did not change significantly, MES decreased at 2 and 6 months and MQS decreased only at 2 months in both groups. The lid margin abnormalities of the non-SS group were significantly improved at 2 and 6 months, while that of the SS group had changes only at 2 months. Interestingly, LLT in non-SS group continued to rise, reaching a higher level at 2 months (p<0.05), while LLT in SS group increased only at 2 months (p<0.05). Meanwhile, after the puntcal plugs insertion, non-SS group showed better outcomes concerning some parameters, such as lower ocular symptom scores, higher TMH and significantly greater LLT, compared with that in SS group (all p<0.05). Conclusions: Our study revealed that dry eye symptoms and signs, including meibomian gland function, improved for at least 6 months in non-SS dry eye patients as well as in SS dry eye patients after punctal plugs insertion.